The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1200/jco.1999.17.12.3810
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Adjuvant Mitomycin Plus Tegafur in Patients With Resected Stage III Gastric Cancer

Abstract: Our positive results are consistent with the results of recent studies; which conclude that there is a potential benefit from adjuvant chemotherapy in resected gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
43
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 37 publications
2
43
1
1
Order By: Relevance
“…A survival benefit has been shown for one regimen vs another (Cirera et al, 1999;Roth et al, 1999;Waters et al, 1999;Chao et al, 2000) and in a small number of studies with small numbers of patients comparing chemotherapy with best supportive care (Murad et al, 1993;Pyrhonen et al, 1995;Glimelius et al, 1997). The absence of a large randomised study of chemotherapy vs best supportive care has allowed the debate on its merits to continue.…”
mentioning
confidence: 99%
“…A survival benefit has been shown for one regimen vs another (Cirera et al, 1999;Roth et al, 1999;Waters et al, 1999;Chao et al, 2000) and in a small number of studies with small numbers of patients comparing chemotherapy with best supportive care (Murad et al, 1993;Pyrhonen et al, 1995;Glimelius et al, 1997). The absence of a large randomised study of chemotherapy vs best supportive care has allowed the debate on its merits to continue.…”
mentioning
confidence: 99%
“…However, the prognosis of patients with locally advanced gastric cancer is generally poor even with curative resection (Noguchi et al, 1989;Shiu et al, 1989;Fuchs and Mayer, 1995). Adjuvant chemotherapy has failed to demonstrate a significant survival benefit for such patients in most randomized trials and meta-analyses, except in a few studies with positive results (Shiu et al, 1989;Krook et al, 1991;Kim et al, 1992;Hermans et al, 1993;Nakazato et al, 1994;Fuchs and Mayer, 1995;Lise et al, 1995;Macdonald et al, 1995;Kelsen, 1996;Kim et al, 1998;Cirera et al, 1999;Earle and Maroun, 1999).…”
mentioning
confidence: 99%
“…The prognosis of patients with locally advanced gastric cancer is generally poor even with curative resection, which is an essential treatment for the long-term survival of patients (Noguchi et al, 1989;Fuchs and Mayer, 1995). Adjuvant chemotherapy has failed to demonstrate a significant survival benefit for such patients in most randomized trials and meta-analyses although a recent study showed improved survival with postoperative chemoradiotherapy compared to surgery alone (Krook et al, 1991;Hermans et al, 1993;Fuchs and Mayer, 1995;Lise et al, 1995;Macdonald et al, 1995;Kelsen, 1996;Kim et al, 1998;Cirera et al, 1999;Earle and Maroun, 1999;Macdonald et al, 2001).…”
mentioning
confidence: 99%